Why did Prophet Muhammad Sallallahu Alayhi Wa Sallam Marry Aisha at the Age of 9 Years Old? - Guru Dev Teeluckdharry (Penerbit Hellow Pustaka, 2025)
According to many Jewish, Christian, and Hindu opponents of Islam, Prophet Muhammad Sallallahu Alayhi Wa Sallam (The Last and Final Prophet of Islam - Peace Be Upon Him) was a sexual pervert and pedophile because he was betrothed to Aisha at the age of 6 years old and married her at the age of 9 years old which is the age of puberty following consummation of the marriage. Many Muslim Scholars, Ulemas, Mawlanas, and Clerics have refuted such a blasphemous allegation through the statement that the marriage of Aisha with Prophet Muhammad Sallallahu Alayhi Wa Sallam (The Last and Final Prophet of Islam - Peace Be Upon Him) occurred due to a Divine Inspiration from ALLAH, The Most Merciful and Most Gracious who knows best.